2018
DOI: 10.5194/acp-18-10199-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modeled deposition of nitrogen and sulfur in Europe estimated by 14 air quality model systems: evaluation, effects of changes in emissions and implications for habitat protection

Abstract: The evaluation and intercomparison of air quality models is key to reducing model errors and uncertainty. The projects AQMEII3 and EURODELTA-Trends, in the framework of the Task Force on Hemispheric Transport of Air Pollutants and the Task Force on Measurements and Modelling, respectively (both task forces under the UNECE Convention on the Long Range Transport of Air Pollution, LTRAP), have brought together various regional air quality models to analyze their performance in terms of air concentrations and wet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…The results showed that the other important factor that explained the differences in SO4 2− concentration between CMAQ and CAMx was SO4 2− wet deposition at EANET observation sites and over domains 3 and 4. A model intercomparison in Europe also concluded that the accurate estimate of deposition is key to an accurate simulation of ambient concentrations [30]. Differences in SO 4 2− concentration were found at Nagoya and Tokyo compared with the high temporal resolution observations; therefore, the analysis for SO 4 2− wet deposition was done over J-STREAM domains 3 and 4, and the results are shown in Figure 11.…”
Section: Wet Deposition Of So 4 2−mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the other important factor that explained the differences in SO4 2− concentration between CMAQ and CAMx was SO4 2− wet deposition at EANET observation sites and over domains 3 and 4. A model intercomparison in Europe also concluded that the accurate estimate of deposition is key to an accurate simulation of ambient concentrations [30]. Differences in SO 4 2− concentration were found at Nagoya and Tokyo compared with the high temporal resolution observations; therefore, the analysis for SO 4 2− wet deposition was done over J-STREAM domains 3 and 4, and the results are shown in Figure 11.…”
Section: Wet Deposition Of So 4 2−mentioning
confidence: 99%
“…The results showed that the other important factor that explained the differences in SO 4 2− concentration between CMAQ and CAMx was SO4 2− wet deposition at EANET observation sites and over domains 3 and 4. A model intercomparison in Europe also concluded that the accurate estimate of deposition is key to an accurate simulation of ambient concentrations[30].…”
mentioning
confidence: 99%
“…The resulting gaseous and particulate nitrogen-and sulfur-containing compounds in the atmosphere can be subsequently deposited to the surface through the mechanisms of wet (in rain, fog or snow) and dry deposition. Within Europe, of the N and S deposition is estimated to come from European emissions (Sanderson et al, 2008;Tan et al, 2018;Vivanco et al, 2018). Over the last 3 decades there has been a reported decrease in European emissions of NO x , NH 3 and SO 2 by approximately 50 %, 15 % and 90 %, respectively (EEA, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, this evaluation can currently only be done for wet deposition, since measurements of dry deposition of N and S are sparse, incomplete and intermittent. Various studies have compared N and S wet deposition estimated by regional and global CTMs with observed values in Europe, giving varying results (Dentener et al, 2006;Simpson et al, 2006Simpson et al, , 2014Vet et al, 2014;Vivanco et al, 2017Vivanco et al, , 2018. Compiling the results of these studies shows that model bias for wet deposition of oxidised ni-trogen ranges from −86 % to +72 % of the average of the observed values with a median bias of −19 %.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the mixing state is more important in the transition from fresh to aged aerosol. The difference be-tween external and internal mixing becomes small when hydrophobic material 100 nm in diameter has a coating of soluble material of 3 nm or more, which may be achieved in a few hours in photo-chemically active environments, such as urban areas during daytime (Wang et al, 2010). The total ERFaci is currently estimated as −0.45 (−1.2 to 0.0) W m −2 (Myhre et al, 2013).…”
Section: Introductionmentioning
confidence: 99%